2001
DOI: 10.1097/00001721-200106000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the tissue factor pathway inhibitor gene and the risk of restenosis after coronary angioplasty

Abstract: Intracoronary stent implantation is associated with a significantly lower risk of restenosis compared with balloon angioplasty. However, restenosis still occurs in some cases. Experimental studies suggest that the tissue factor pathway is involved in this phenomenon. We investigated a possible relationship between three previously identified polymorphisms of the tissue factor pathway inhibitor (TFPI) gene and restenosis in 443 patients who underwent angioplasty, with or without stent implantation. The effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
5
19
0
1
Order By: Relevance
“…Their study did not support an association between TFPI polymorphism and acute coronary syndrome. The same authors 64,65 reported no link between this mutation and venous thromboembolic disease or restenosis after coronary angioplasty. Polymorphism in the promoter region of TFPI was not associated with the plasma level of TFPI or with venous thrombosis.…”
Section: Plasma Tfpi Levels In Various Diseasesmentioning
confidence: 96%
“…Their study did not support an association between TFPI polymorphism and acute coronary syndrome. The same authors 64,65 reported no link between this mutation and venous thromboembolic disease or restenosis after coronary angioplasty. Polymorphism in the promoter region of TFPI was not associated with the plasma level of TFPI or with venous thrombosis.…”
Section: Plasma Tfpi Levels In Various Diseasesmentioning
confidence: 96%
“…Miyata et al [17], however, found that this polymorphism was not related to total TFPI levels and its prevalence was unaltered among Japanese control individuals and patients with deep vein thrombosis. The CC genotype of the intron 7 C-33T polymorphism has been shown to be independently associated with a decrease in venous thromboembolism risk, but not with acute coronary events or restinosis after angioplasty [11,12,18]. In addition, this polymorphism is associated with increased total TFPI levels, but not free levels, in healthy control individuals [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this polymorphism is associated with increased total TFPI levels, but not free levels, in healthy control individuals [11,12]. Moatti et al [18] also demonstrated that the CC genotype is associated with higher total TFPI levels in women who suffered a deep vein thrombosis. Several studies have examined the V264M polymorphism [10,12,19], and while some have found an association with total TFPI none have linked it to coronary artery disease, venous thromboembolism or deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The 399T>C polymorphism was found to be associated with lower plasma TFPI levels and increased plasma F1 + 2 levels, a marker of increased coagulation [21]. Similarly, a combination of 287T T within intron 7-33T T was associated with low plasma TFPI levels [22]. In addition, higher plasma TFPI levels were observed in patients carrying the -33CC polymorphism in intron 7 [23].…”
Section: Tissue Factor Pathway Inhibitor Polymorphisms and Thrombosismentioning
confidence: 99%